Biogas from Food Waste on the Island of Tenerife: Potential from Kitchens and Restaurants, Stabilisation and Conversion in a Biogas Plant Made of Textile Materials - Verónica Hidalgo-Sánchez; María Emma Borges; Josef Hofmann; Daniel Cuñarro; Sophie Schneider; Tobias Finsterwalder (Applied Sciences, 2025)
Municipal solid waste management (MSWM) on islands involves several challenges relating to politics, society, the environment, and technology. This paper addresses the potential for producing biogas and biomethane from food waste on Tenerife, including waste from households, with the aim of reducing landfill and primary fossil energy consumption. The study also introduces the European and Regional policy framework and requirements. Effective microorganisms have been studied as proposals to stabilise the food waste from households, avoiding odours and decomposition during storage. The trials show positive results in terms of the preservation of organic matter until the food waste is transported to the biogas plant. In addition, a new concept for a small biogas plant made of textile materials, which are suited to the municipalities of Tenerife, is presented to provide an easy-to-build solution, with ranges of up to 75 kW in electrical power. With a theoretical potential of 299,012 tons of food waste being available per year (based on 2022), preliminary laboratory experiments with real samples of the island showed a theoretical potential of 28.97 × 106 Nm3 for biogas and 264,612 tons for digestate, which can be used as fertilisers, with potential savings of 18.15 × 106 L of gasoline and 42.66 × 103 equivalent CO2 tons.